Novel nested patch-based feature extraction model for automated Parkinson's Disease symptom classification using MRI images - Kaplan, Ela; Altunisik, Erman; Firat, Yasemin Ekmekyapar; Barua, Prabal Datta; Dogan, Sengul; Baygin, Mehmet; Acharya, U. Rajendra (Elsevier Ireland Ltd, 2022)
Objective: Parkinson's disease (PD) is a common neurological disorder with variable clinical manifes-tations and magnetic resonance imaging (MRI) findings. We propose a handcrafted image classification model that can accurately (i) classify different PD stages, (ii) detect comorbid dementia, and (iii) discrim-inate PD-related motor symptoms.Methods: Selected image datasets from three PD studies were used to develop the classification model. Our proposed novel automated system was developed in four phases: (i) texture features are extracted from the non-fixed size patches. In the feature extraction phase, a pyramid histogram-oriented gradient (PHOG) image descriptor is used. (ii) In the feature selection phase, four feature selectors: neighborhood component analysis (NCA), Chi2, minimum redundancy maximum relevancy (mRMR), and ReliefF are used to generate four feature vectors. (iii) Two classifiers: k-nearest neighbor (kNN) and support vector machine (SVM) are used in the classification step. A ten-fold cross-validation technique is used to validate the results. (iv) Eight predicted vectors are generated using four selected feature vectors and two classi-fiers. Finally, iterative majority voting (IMV) is used to attain general classification results. Therefore, this model is named nested patch-PHOG-multiple feature selectors and multiple classifiers-IMV (NP-PHOG-MFSMCIMV).Results: Our presented NP-PHOG-MFSMCIMV model achieved 99.22, 98.70, and 99.53% accuracies for the collected PD stages, PD dementia, and PD symptoms classification datasets, respectively.Significance: The obtained accuracies (over 98% for all states) demonstrated the performance of developed NP-PHOG-MFSMCIMV model in automated PD state classification.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: PD image classification; Nested patch division; Local binary pattern; Local phase quantization; Neighborhood component analysis; Image classification